2019
DOI: 10.1037/xge0000511
|View full text |Cite
|
Sign up to set email alerts
|

Sensory noise increases metacognitive efficiency.

Abstract: Visual metacognition is the ability to employ confidence ratings in order to predict the accuracy of one's decisions about visual stimuli. Despite years of research, it is still unclear how visual metacognitive efficiency can be manipulated. Here we show that a hierarchical model of confidence generation makes a counterintuitive prediction: Higher sensory noise should increase metacognitive efficiency. The reason is that sensory noise has a large negative influence on the decision (where it is the only corrupt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 72 publications
(143 reference statements)
11
81
0
Order By: Relevance
“…The hierarchical model proposes that metacognition and primary decision-making are two distinct cognitive processes: the primary decision-making is implemented at a first order, while a metacognitive process access both sensory evidence for the decision-making and other sources of information to form a judgement (Fleming & Daw, 2017). Many studies have reported such dissociation between metacognition and decision-making, with the PFC playing a central role in the hierarchical monitoring (Allen et al, 2017;Bang et al, 2019;Fleming et al, 2014;Hauser et al, 2017b;Qiu et al, 2018;Rounis et al, 2010;Shekhar and Rahnev, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The hierarchical model proposes that metacognition and primary decision-making are two distinct cognitive processes: the primary decision-making is implemented at a first order, while a metacognitive process access both sensory evidence for the decision-making and other sources of information to form a judgement (Fleming & Daw, 2017). Many studies have reported such dissociation between metacognition and decision-making, with the PFC playing a central role in the hierarchical monitoring (Allen et al, 2017;Bang et al, 2019;Fleming et al, 2014;Hauser et al, 2017b;Qiu et al, 2018;Rounis et al, 2010;Shekhar and Rahnev, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We sought to build a generative model that preserves the assumptions of SDT (Green and Swets, 1966) at the level of the perceptual decisions but also allows us to explicitly model the transformations to the sensory signal that are responsible for generating the confidence ratings. The simplest way to model the transformation of the sensory signal at the metacognitive level is to postulate the existence of metacognitive noise that corrupts the sensory signal as done previously by the creators of the meta-d′ measure (Maniscalco and Lau, 2014), us (Rahnev et al, 2016; Bang et al, 2017) and others (Mueller and Weideman, 2008; Jang et al, 2012; De Martino et al, 2013; van den Berg et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, many other experiments imply the presence of dissociable neural circuits for perceptual decision making and confidence. Behaviorally, confidence judgments can be dissociated from the accuracy of the perceptual decision in both humans (Lau and Passingham, 2006;Rahnev et al, 2011bRahnev et al, , 2015Zylberberg et al, 2012Zylberberg et al, , 2016Vlassova et al, 2014;Spence et al, 2015;Koizumi et al, 2015;Song et al, 2015;Samaha et al, 2016Samaha et al, , 2017Boldt et al, 2017;Peters et al, 2017;Desender et al, 2018) and monkeys (Ferrigno et al, 2017), whereas other studies suggest that confidence judgments but not perceptual decisions are subject to late metacognitive noise (Mueller and Weidemann, 2008;Jang et al, 2012;De Martino et al, 2013;Maniscalco and Lau, 2016;Rahnev et al, 2016;van den Berg et al, 2017;Shekhar and Rahnev, 2018;Bang et al, 2019). Neurally, studies employing transcranial magnetic stimulation (TMS) delivered to the prefrontal cortex have been able to alter subjects' confidence ratings, while leaving their perceptual decisions unaffected (Rounis et al, 2010;Fleming et al, 2015;Rahnev et al, 2016;Shekhar and Rahnev, 2018).…”
Section: Introductionmentioning
confidence: 99%